The Language of Success: A Needs Analysis of the Ideal English for Business Learning Program Based on Professional Insights - Maulana, Rivki Surya; Siti Nurul Azkiyah; Ratna Sari Dewi; Kustiwan (Institut Agama Islam Negeri Palopo, 2025)
This study investigates the critical role of English proficiency in career advancement and business growth, focusing on the characteristics of an ideal Business English course. The research employs a qualitative approach, using interviews and focus group discussions with seven employees from various industries to gather insights. Findings reveal a preference for small classroom settings (3-5 people) where instruction is delivered entirely in English. Participants believe that such settings provide personalized attention and foster interactive learning experiences, which are more effective for mastering the language. However, several challenges were identified, including low self-esteem, mockery from peers, and a lack of learning partners. Low self-esteem and fear of ridicule discourage active participation and practice, while the absence of learning partners outside the classroom limits opportunities to reinforce skills. This study highlights the necessity of tailored Business English courses that focus not only on language proficiency but also on the unique challenges faced by adult learners. By addressing these challenges, such courses can enhance professional communication skills, contributing to individual career success and business growth. This research underscores the importance of a holistic approach to Business English education, which considers both the instructional environment and the psychological needs of learners.